2000
DOI: 10.1093/carcin/21.8.1537
|View full text |Cite
|
Sign up to set email alerts
|

A potential mechanism for fumonisin B 1 -mediated hepatocarcinogenesis: cyclin D1 stabilization associated with activation of Akt and inhibition of GSK-3β activity

Abstract: Fumonisin B(1) (FB(1)) is a worldwide corn contaminant and has been epidemiologically linked to the high incidence of human esophageal cancer in South Africa and China. FB(1) is hepatocarcinogenic in rats by an unknown mechanism. Inhibition of ceramide synthase and disruption of membrane phospholipids have been shown to be mechanisms of toxicity. Here we show overexpression of cyclin D1 protein in both preneoplastic and neoplastic liver specimens obtained from a long-term feeding study of FB(1) in rats. In rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…ArtinM treatment increased nuclear p21 and p27 staining which could restore their tumor-suppressing function. Moreover, previous studies reported the importance of cyclin D-CDK complex for cell cycle transition and the intrinsic relationship between p21 levels and cyclin D1 activity (29,30). In accordance, animals exposed to DEN, showed a significant increase of cyclin D levels, which were restored to same levels as in the control group by ArtinM treatment.…”
Section: Discussionsupporting
confidence: 58%
“…ArtinM treatment increased nuclear p21 and p27 staining which could restore their tumor-suppressing function. Moreover, previous studies reported the importance of cyclin D-CDK complex for cell cycle transition and the intrinsic relationship between p21 levels and cyclin D1 activity (29,30). In accordance, animals exposed to DEN, showed a significant increase of cyclin D levels, which were restored to same levels as in the control group by ArtinM treatment.…”
Section: Discussionsupporting
confidence: 58%
“…For examples, growth suppressive treatments decreased cyclin D1 protein synthesis with minimal changes in message levels (Brewer and Diehl, 2000;Mettouchi et al, 2001;Muise-Helmericks et al, 1998;Palakurthi et al, 2000;Pervin et al, 2001). Fumonisin B1, a carcinogenic mycotoxin, stabilizes cyclin D1 protein resulting in high levels of protein expression without a change in message levels (Ramljak et al, 2000). Growth suppressive chemicals can also destabilize cyclin D1 message and/or protein (Agami and Bernards, 2000;Dufourny et al, 2000, Hashemolhosseini et al, 1998Lin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since proTGFa translocates to the nucleus in the G1-phase of the cell cycle (Grasl-Kraupp et al, 2002), the elevated presence of nuclear proTGFa in (pre)malignant hepatocytes may be evidence for a G1-status of these cells. Several groups reported that premalignant liver cells show an increased expression of c-myc and cyclin D1, known inducers of the transition from G0 to G1 of the cell cylce (Deguchi and Pitot, 1995;Ramljak et al, 2000). On the other hand, the expression of the WAF1/CIP1 gene product, p21 and the c-myc antagonist mad were decreased in hepatocarcinogenesis (Martens et al, 1996).…”
Section: Discussionmentioning
confidence: 99%